Regional Social and Economic Concern of Supply Chain Sustainability in Republic Of Tatarstan - S.V. Khusainova; E.A. Osadchy; S.Y. Bakhvalov; O.N. Ustyuzhina (International Journal of Supply Chain Management, 2020)
Abstract— Sustainability of supply chains is achieved through the consideration of the economic, environmental and social aspects in the decision making process.  There is an objective need to systematize knowledge about the peculiarities of the competitiveness of municipalities, identify factors that determine the competitive position of municipalities, and search for new supply chain management that allow improving and supplementing existing mechanisms for managing the competitiveness of municipal economic systems, as well as managing the competitiveness and socio-economic development of municipalities. The economic pillar of sustainability is addressed in this work considering the costs of the supply chain. In this regard, the sphere of culture should be considered as an integral part of the mechanism for forming the competitiveness of the national municipality of the Republic of Tatarstan. Valid approaches have been formulated for estimating the economic effects of supply chain strategy on regional economy and for identifying critical backward commodities. Using the developed approaches, the case study shows that local procurement strategy can significantly affect the regional economy